Assessment of Infection Control Process at Hemodialysis Units in Kurdistan Region - Khalida A.M.Al-Gersha (Iraqi National Journal of Nursing Specialties, 2023)
Objective: to assess the infection control process in hemodialysis units and to find out the relation ship between nurses practices and some of the demographic characteristics. Methodology:٨descriptive study was conducted at hemodialysis units in Hawler hospital and Azad hospital in Duhok Governorate, from 15th of January2004 to the end of May 2005 Non-probability Sampling was performed, a purposive sample of (40) Nurses who worked in hemodialysis units, a purposive sample of (63) patients who were attending to the hemodialysis unit at time of the data collection ,and taking swab from different site of vascular access (fistula, shunt).٨ checklist was constructed by investigator in regard to the purpose of the present study which included the different tools were used through the data collection. part one: -٨ checklist for environmental precaution concerning infection control. Part two: A-questioner for Sociodemographic characteristic for nurses. B - observational checklist form for nursing practice concerning infection Control. Part three: -٨ questioner for socio and clinical demographic of ([559) patient B- patient practice concerning infection Control. Part four: Swab specimens were also gathered from vascular access site. Content validity of the checklist was responses through panel of (16) experts. Reliability of checklist was determined through use of inter-observer questionnaire for nursing practice and the test- retest for patient practice. Results: The results of the study revealed that the presents of isolate room at hemodialsis unit for patients with HBV. The result also revealed that the standard precaution that was applied in dialysis unit concerning infection control was adequate application of standard precaution of ventilation with ٠ College of Nursing/ University of Irbil ٠٠ Adult Nursing Department /College of NursingاUniversity of Baghdad 74 Infection Control Process at Hemodialysis Units grand mean of Score (2.00), sterilization of the dialysis machine, and walls and floor cleaning with grand mean of score (1.85). The data analysis indicated that the majority of nurses were male, with age group (21-30) years. And more than half of them graduated from institute. The result also indicated (82.5%) of nurses had (1-3) years of experience in hemodialysis (95%) had no training session after graduation. Concerning nurse’s practice, the data revealed inadequate practices related to cleaning patient’s bed and linens management, fistula care and instrument preparation, isolation room, sharp equipment management, drugs administration management and instruction. Significant differences were found between nurse’s practices and place of work, and no significant differences were found between nurse’s practice concerning infection control and certain variables such as sex, age, marital status, level of education and years of experience in hemodialysis and peritoneal dialysis. The result shows that the half of patients of dialysis were male, their age ranged between (51-60) years and had (1-5) years history of renal failure. Regarding patient practice, the patient had high mean ofscore for doing laboratory tests. Recommendation: The study recommended that the periodic evaluation for the environmental nurse’s practices concerning infection control at dialysis unit and continuous training and education should be conducted for all the nursing staff.